Chemical Exposure to Polycyclic Aromatic Hydrocarbons and Hematological Evaluation among Petrol Pump Workers in Islamabad, Pakistan. (21st October 2022) - Sahar, Sumia; Rashid, Audil; Hua, Rimao; Naseem, Faiza; Batool, Aniqa
Abstract: Petroleum goods are extensively consumed in urban areas and cause hazardous effects on individuals related to petroleum related occupations. Chemical exposure of petrol pump workers to petroleum hydrocarbons such as polycyclic aromatic hydrocarbons (PAHs) is unprecedented in Pakistan. We conducted a prospective cohort study to analyze the risk of PAH exposure on hematological anomalies and health symptoms of petrol pump workers. Blood samples of 50 individuals were collected which include petrol pump workers (n = 30) and unexposed controls (n = 20). Serum phenanthrene and pyrene concentrations (µg ml −1 ) were estimated utilizing High Performance Liquid Chromatography (HPLC) whereas hematological parameters were analyzed by subjecting samples to count Hematocrit, Hemoglobin white and red cells in the blood. Correlation and binary logistic regression analyses were performed to depict association for individual's exposure with demographic variables and for the prediction of eye-irritation as health risk symptom among petrol pump workers. Results show that hematological parameters are affected by occupational exposure to PAHs while eye-irritation is relatively significant for smokers than the nonsmokers in exposed group (OR = 0.109, 95%; C.I = 0.013–0.881) ( p  < 0.05). Our study concludes that phenanthrene and pyrene poses serious health risk among petrol pump workers owing to their inevitable PAH exposure.